Consumer valuation of health attributes in food - Sinne Smed; Lars Gårn Hansen (University of Copenhagen, Department of Food and Resource Economics (IFRO), 2016)
Numerous studies find that education and the healthiness of diets are highly correlated. One possible explanation is that the most highly educated consumers are better at understanding and appreciating the health implications of their diet than consumers with less lower education. In this study, we estimate a hedonic model of consumers' valuation of food characteristics that allows nutrients to influence utility both through their perceived effects on health and through their effects on the taste and consumption experience. We find that the most highly educated have the same or lower revealed preferences for health compared to the least educated, and we find that it is differences in taste preferences, not differences in health preferences, that explain why the most highly educated have a healthier diet.
Keywords: D12; I12; 330; hedonic model; taste; health; food consumption